2016
DOI: 10.1007/s13202-016-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of confining stress on permeability of tight gas sands: an experimental study

Abstract: Stress influence on permeability has been extensively studied by various authors, as the stress can significantly affect reservoir's productivity. This paper displays the features of permeability stress sensitivity in tight gas sandstone in Kirthar fold belt lower Indus Basin, Sindh, Pakistan. The experiments performed under a range of pore pressure and confining stress, and the results were analyzed by integrating with microstructural observations. The results obtained were used, to explore the combined effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Pressure. As shown in Figures 15-19, the permeability of the coal specimen decreases exponentially with the increase of confining pressure under the same axial strain, which is in good agreement with previous studies [18][19][20]. At the initial stage of confining pressure loading, the permeability of water-bearing coal decreases rapidly.…”
Section: The Evolution Of Permeability Versus Confiningsupporting
confidence: 89%
See 1 more Smart Citation
“…Pressure. As shown in Figures 15-19, the permeability of the coal specimen decreases exponentially with the increase of confining pressure under the same axial strain, which is in good agreement with previous studies [18][19][20]. At the initial stage of confining pressure loading, the permeability of water-bearing coal decreases rapidly.…”
Section: The Evolution Of Permeability Versus Confiningsupporting
confidence: 89%
“…Some experts [16][17][18] studied the permeability of coal measured rock under cyclic loading and unloading, concluding that the unloading curve of rock did not coincide with the loading curve, forming a closed plastic hysteresis loop, and also obtained the evolution of residual strain with the cyclic times and the damage evolution of coal measured rock. Besides, the relation between confining pressure and permeability was researched [19][20][21][22][23][24][25][26]. The experiments and numerical results indicated that the relationship of confining pressure and coal permeability could be described by an exponential function.…”
Section: Introductionmentioning
confidence: 99%
“…9) could be the samples permeability heterogeneity. Authors [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] have proposed that the scatter in between permeability and gas slip factor might be the result of experimental error. In carbonate rock samples having high slippage factor values and high permeability associated with smaller pore radius has also reported by [27].…”
Section: Fig 8 Plot Shows the Fitting Curves Of The Gas Permeabilitmentioning
confidence: 99%
“…Though, the country will remain dependent on fossil fuels in upcoming years as the renewables have recently emerges in a very small quantity. Pakistan is rich in both conventional and unconventional hydrocarbon resources [5][6][7]. Pakistan's most of the sedimentary basins possess significant reserves of oil and gas in both offshore and on shore areas; however, the country suffers from the lack of advanced technology and poor policy practices [3].…”
Section: Introductionmentioning
confidence: 99%